Ciliary protein conservation during development in the ciliated protozoan, Oxytricha (The Rockefeller University Press, 1987)
The ciliated protozoan Oxytricha fallax possesses multiple highly localized clusters of basal bodies and cilia, all of which are broken down and rebuilt during prefission morphogenesis-with one major exception. The adoral zone of membranelles (AZM) of the ciliate oral apparatus contains approximately 1,500-2,000 basal bodies and cilia, and it is the only compound ciliary structure that is passed morphologically intact to one daughter cell at each cell division. By labeling all proteins in cells, and then picking the one daughter cell possessing the original labeled AZM, we could then evaluate whether or not the ciliary proteins of the AZM were diluted (i.e., either by degradation to constituent amino acids or by subunit exchange) during cell division. Autoradiographic analysis demonstrated that the label was highly conserved in the AZM (i.e., we saw no evidence of turnover), and electrophoretic data illustrate that at least one of the proteins of the AZM is tubulin. We, therefore, conclude that for at least some of the ciliary and basal body proteins of Oxytricha fallax, AZM morphological conservation is essentially equivalent to molecular conservation.